1993
DOI: 10.1099/0022-1317-74-2-265
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear cells are not sites of persistence of human cytomegalovirus in healthy individuals

Abstract: Polymorphonuclear leukocytes (PMNL) have been shown to harbour human cytomegalovirus (HCMV) in viraemic patients, but to date PMNL of asymptomatic healthy subjects have not been examined directly to determine whether this is a normal site of HCMV persistence. Using the polymerase chain reaction (PCR), paired DNA samples prepared from adherent peripheral blood mononuclear cells (PBMC), which are known to be a site of persistence of HCMV, and PMNL of 10 healthy adults were analysed. All of seven individuals who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
52
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 15 publications
5
52
0
Order By: Relevance
“…In contrast, the lack of morphological alterations as well as the absence of any detectable early and late viral antigens in infected PMNL indicates that these cells are only abortively infected. In agreement with this are analyses on PMNL from peripheral blood, in which no synthesis of late viral antigen could be demonstrated (Taylor-Wiedeman et al, 1993;Grefte et al, 1992). Taken together, compared with the conflicting data from earlier in vivo studies based on histopathology alone, the immunohistochemical double staining analysis corresponded much better with the replication of HCMV in cell culture systems.…”
Section: Sinzger and Otherssupporting
confidence: 74%
“…In contrast, the lack of morphological alterations as well as the absence of any detectable early and late viral antigens in infected PMNL indicates that these cells are only abortively infected. In agreement with this are analyses on PMNL from peripheral blood, in which no synthesis of late viral antigen could be demonstrated (Taylor-Wiedeman et al, 1993;Grefte et al, 1992). Taken together, compared with the conflicting data from earlier in vivo studies based on histopathology alone, the immunohistochemical double staining analysis corresponded much better with the replication of HCMV in cell culture systems.…”
Section: Sinzger and Otherssupporting
confidence: 74%
“…Accumulating evidence has shown that HCMV is carried latently in mononuclear cells of the myeloid lineage during lifelong latency in naturally infected individuals (5)(6)(7)(8). Differentiation of monocytes to macrophages in vitro is reported to induce immediate-early (IE) lytic gene expression from latent virus (9), and groups have intermittently reported that infectious virus can be recovered after differentiation of monocytes to macrophages through explant culture (10) and, more recently, by allogeneic T cell stimulation (11), suggesting that reactivation of latent virus is associated with both the differentiation and activation state of myeloid cells.…”
mentioning
confidence: 99%
“…Interestingly, monocytes are primary HCMV target cells in vivo and are responsible for dissemination of the virus throughout the body during the latent, acute, and late phases of infection. Thus, the monocyte represents a key cell type in the pathogenesis of HCMV infection, since this cell type represents an important cellular reservoir for latent virus (45,50,51). A number of studies have shown that HCMV infection in monocytes is nonpermissive (11,34) and that cellular differentiation is a prerequisite for HCMV replication (13,18,42,46,52).…”
mentioning
confidence: 99%